Survival and predictors of mortality among preterm neonates in Northern Ethiopia: A retrospective follow-up study - Girma, Bekahegn; Berhe, Hailemariam; Mekonnen, Furtuna; Nigussie, Jemberu (Frontiers in Pediatrics, 2023)
Background: Globally, in 2015, above 1/3 of neonatal mortality was recorded due to prematurity. Despite different efforts taken on globally and locally to reduce neonatal mortality; the mortality remains high with a low reduction rates, especially in low and middle-income countries like Sub-Saharan Africa and South Asia. Therefore; this study aimed to assess the survival status and predictors of mortality among preterm neonates. Methods: A retrospective follow-up study was conducted on randomly selected 561 preterm neonates. Data were extracted from patient records using a pretested checklist. Data entry and analysis were done using Epi Data Version 4.4.2.1 and Stata version 14, respectively. Cox proportional hazard regression model was fitted to identify the predictors of mortality. A hazard ratio with a 95% confidence interval was estimated and p-values < 0.05 were considered statistically significant. Result: The proportion of preterm neonatal death was 32.1% (180) with an incidence of 36.6 (95% CI: 31.6-42.4) per 1000 person-days. The mean survival time was 18.7 (95% CI: 17.7-19.9) days. The significant predictors for time to death of preterm neonates were respiratory distress syndrome (AHR: 2.04; 95%CI: (1.48-2.82)), perinatal asphyxia (AHR: 2.13; 95% CI: (1.32-3.47)), kangaroo mother care (AHR: 0.14; 95% CI: (0.08-0.24)) and gestational age (AHR: 0.85; 95% CI: (0.80-0.90)). Conclusion: Preterm neonatal death is still a major public health concern. Respiratory distress syndrome, perinatal asphyxia, kangaroo mother care, and gestational age were independent significant predictors for time to death. Hence, it is better to give priority to neonates with the above illnesses and strengthen the management and the care provided for preterm neonates.